1989
DOI: 10.1182/blood.v73.5.1351.bloodjournal7351351
|View full text |Cite
|
Sign up to set email alerts
|

Endogenously generated activated killer cells circulate after autologous and allogeneic marrow transplantation but not after chemotherapy

Abstract: After marrow transplantation, major histocompatibility complex (MHC)- unrestricted natural killer (NK) lymphocytes are among the first cells to appear in the circulation. After T-cell-depleted bone marrow transplantation (TD-BMT), these cells have an activated pattern of target cell killing; they also secrete lymphokines including gamma- interferon (gamma-IFN), interleukin-2 (IL-2), and tumor necrosis factor (TNF) and may have a significant role as a primary defense against viral reactivation and in the elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In allogeneic transplantation, increases in plasma levels of both INFg and IL-2 have been associated with graft-versusleukaemia (Hauch et al, 1990;Chasty et al, 1993) and graftversus-host effects (Neiderweisser et al, 1990). Both of these cytokines increase NK activity which are thought to be the principal effectors in allogeneic transplants (Reittie et al, 1989;Hauch et al, 1990). In MM patients the contribution of NK cells to an autologous anti-tumour effect is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In allogeneic transplantation, increases in plasma levels of both INFg and IL-2 have been associated with graft-versusleukaemia (Hauch et al, 1990;Chasty et al, 1993) and graftversus-host effects (Neiderweisser et al, 1990). Both of these cytokines increase NK activity which are thought to be the principal effectors in allogeneic transplants (Reittie et al, 1989;Hauch et al, 1990). In MM patients the contribution of NK cells to an autologous anti-tumour effect is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are relatively spared by CAMPATH-1, 41, 45 and it has been suggested that they may play a role in control of CMV disease and have an antileukemia effect. [46][47][48][49][50][51] However, B cells are efficiently depleted. Elsewhere, we have reported that T-cell depletion with CAMPATH-1 antibodies does not give rise to an excess of B-cell lymphoproliferative disorders, in contrast to some other methods of T-cell depletion.…”
Section: Discussionmentioning
confidence: 99%